2012
DOI: 10.1016/j.ajhg.2012.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Revertant Somatic Mosaicism by Mitotic Recombination in Dyskeratosis Congenita

Abstract: Revertant mosaicism is an infrequently observed phenomenon caused by spontaneous correction of a pathogenic allele. We have observed such reversions caused by mitotic recombination of mutant TERC (telomerase RNA component) alleles in six patients from four families affected by dyskeratosis congenita (DC). DC is a multisystem disorder characterized by mucocutaneous abnormalities, dystrophic nails, bone-marrow failure, lung fibrosis, liver cirrhosis, and cancer. We identified a 4 nt deletion in TERC in a family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 34 publications
3
70
0
Order By: Relevance
“…Although the reversion may have protected against the bone marrow failure phenotype in the proband, to date, reversion has not been detected before the age of 40 years. 22 It is, therefore, possible that the missense mutation in this family represents a hypomorphic allele.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the reversion may have protected against the bone marrow failure phenotype in the proband, to date, reversion has not been detected before the age of 40 years. 22 It is, therefore, possible that the missense mutation in this family represents a hypomorphic allele.…”
Section: Discussionmentioning
confidence: 99%
“…Somatic reversion is known to occur in genome instability syndromes and has been described in patients with dyskeratosis congenita with TR mutations. 22 In these cases, homologous recombination mediates reversion to the wild-type allele in the blood. 22 In our study, however, we found evidence suggesting an acquired clonal event in the blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De novo mutations, germline mosaicism and other complexities Although this concept of somatic mosaicism has been in the literature for many years [131][132][133][134][135], it is really only recently that more people are beginning to realize that it might be much more extensive in humans than previously thought [23,[136][137][138][139][140][141][142][143][144][145][146][147][148][149]. In fact, hardly anything is truly known regarding the extent of somatic mosaicism in humans and its effect on phenotype in even well studied diseases.…”
Section: "Those Who Have Given Any Attention To Congenital Mental Lesmentioning
confidence: 99%
“…TERC and TERT mutations (5%-10% each of all cases) are found in autosomal dominant and recessive DC and show disease anticipation, such that successive generations not only inherit the genetic lesion but also have shorter telomeres, which may produce an earlier onset of clinical manifestations (8 ). Somatic reversion of the TERC gene, likely driven by a resulting selective growth advantage in hematopoietic stem cells, has been observed in DC and is a potential confounder of genetic testing (9 ). With sufficient clinical concern, a normal result in a TERC analysis of peripheral blood DNA should be followed by testing of other somatic cells.…”
Section: Patient Follow-upmentioning
confidence: 99%